Single-sex mathematics classes: Who benefits? - Forgasz , Helen J.; Leder, Gilah C. (NOMAD Nordic Studies in Mathematics Education, 1995)
A co-educational high school in Melbourne, Australia, introduced an innovative program of single-sex mathematics classes for grade 10 students. Of particular concern to the school was the impact of the program on enrolments in mathematics courses in grade 11. The requested evaluation of the program is reported in this paper. Students' and parents' reactions, the effects on students' achievements and their beliefs about themselves as learners of mathematics are presented. Implications of the findings and recommendations to the school for future action are discussed.